1991
DOI: 10.1037/0022-006x.59.4.594
|View full text |Cite
|
Sign up to set email alerts
|

Relation between differential emotions and depression in emotionally disturbed children and adolescents.

Abstract: Differential emotions theory (Izard, 1972) provides a conceptual framework for the role of emotions in affective disorders. The present study investigated the relation of emotions to depression in a sample of child and adolescent psychiatric inpatients (N= 145). Findings indicate that shyness, anger, enjoyment, and shame explained 51.4% of the variance in depression scores. Furthermore, profiles of emotions experienced by youths with a depressive disorder differed significantly from emotion profiles of nondepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…Another important consideration that has not been examined in previous studies is potential confounding effects of psychiatric symptoms in the association between emotions and SI. Because certain emotions may be more likely than others to co‐occur with symptoms of depression (Carey, Carey, & Kelly, 1997; Carey, Finch, & Carey, 1991) and anxiety (Etkin & Wager, 2007), it is potentially more informative to examine the relationships of emotions with SI over and above the severity of psychiatric symptoms.…”
mentioning
confidence: 99%
“…Another important consideration that has not been examined in previous studies is potential confounding effects of psychiatric symptoms in the association between emotions and SI. Because certain emotions may be more likely than others to co‐occur with symptoms of depression (Carey, Carey, & Kelly, 1997; Carey, Finch, & Carey, 1991) and anxiety (Etkin & Wager, 2007), it is potentially more informative to examine the relationships of emotions with SI over and above the severity of psychiatric symptoms.…”
mentioning
confidence: 99%
“…The findings of Izard (1985, 1986) revealed that the emotions of sadness, self-directed hostility, anger, shame, interest, and enjoyment contributed to the prediction of depressive symptomatology in non-referred 10-and 11-year old children. Moreover, research with reliably DSM-III-R (American Psychiatric Association, 1987) diagnosed adolescent psychiatric patients indicated that the emotional configuration of depressed adolescents differed from non-depressed youths on the emotions of enjoyment, surprise, sadness, anger, shame, shyness, guilt, and self-directed hostility (Carey, Finch, & Carey, 1991). These studies provide support for the role of emotions in depressive symptomatology.…”
mentioning
confidence: 79%
“…Nine DES factors (sadness, hostility, anger, fear, interest, enjoyment, shame, guilt, and shyness) were chosen a priori for this study. The available studies on the DES with children and adolescents have demonstrated adequate reliability and validity (Blumberg & Izard, 1985, 1986Carey, Finch, & Carey, 1991).…”
Section: Reynolds Adolescent Depression Scale (Rads)mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the problem of co-occurrence of comorbidity of symptoms, it is normal for a child who exhibits symptoms of depression to also exhibit some symptoms of anxiety, social withdrawal, somatic complaints, and vice-versa. Also, recent research has indicated that various expressions of affectivity (i.e., positive affect and negative affect) may keenly impact the expression of internalizing disorders of children and may be a key to differentiating depression from anxiety in cases where such differentiation is possible (e.g., Carey, Finch, & Carey, 1991;Jolly, Dyck, Kramer, & Wherry, 1994;Stark, Kaslow, & Laurent, 1993;Tellegen, 1986;Watson & Clark, 1984). The unique broad-band internalizing symptom construction of the ISSC, coupled with its affect-based factor structure, are consistent with these recent developments in child psychopathology research.…”
Section: Instrumentmentioning
confidence: 99%